Planting for honeybees the grower's guide to creating a buzz - Wyndham Lewis, Sarah (Quadrille, 2018)
"Our gardens would be unrecognizable without the gentle buzz of the humble honeybee. Yet in recent years bee populations have suffered from th loss of green spaces and need our help. Planting for Honeybees is a charmingly illustrated, practical guide on how to help attract these delightful pollinators - whether you only have a city window ledge or a whole country garden. With advice on the blooms to grow, and when and where to plant them, this book reveals the tips and tricks to creating a buzz and a better future for our apian friends.--COVER."